Ambivalent impact of customer satisfaction on firm value in emerging markets: the case of Korea - Kim, Hyunseok; Kim, Jaisang; Choi, Kyeong-Seop (Journal of Business Economics and Management, 2017)
Many researchers report that American Customer Satisfaction Index relates significantly and positively to firm value. The purpose of this paper is to examine whether such relation holds in the emerging markets such as Korea. Our preliminary OLS analysis reports that Korean customer satisfaction is irrelevant to firm value. Quantile regressions, applied for further analysis, report that customer satisfaction can be detrimental to firm value if the firm is enjoying the higher kind of value. These results undermine efforts, on the theoretical level, to establish Customer Satisfaction Index as a consolidated firm-value indicator; furthermore, managerial efforts to boost up firm value by managing customer satisfaction lose ground in the emerging markets. This study also corroborates Reinartz and Kumar’s (2002) marketing insight that to satisfy customers, make them loyal, is trivial for profitability and firm value in Korea perspective. The practical implication of our finding is that the relation between customer satisfaction and firm value becomes more ambiguous, especially when it is considered in the emerging market contexts. It also provides management with a fresh new insight that they should take prudence when they increase expenses on customer satisfaction since it turned out to be not a “panacea”.